Deconstructing the nation : the Abbey Theatre and stage-Irishness on screen, 1930-1960 - Monahan, Barry (Trinity College (Dublin, Ireland). Department of Film, 2004)
This thesis examines the consequences for representations of the national through national discourses of the increasing artistic and technical collaboration that occurred between the Abbey Theatre and a number of film producers interested in representing Ireland on screen during the period from 1930 - 1960. Of principal importance is the changing role of the stage-Irishman (and, more broadly, stage-Irishness) as national stereotype as it evolved from stage to screen, and was framed within the second medium. Several theatrical contingencies were to play a significant role in the way “Irishness” was constructed on screen at a crucial moment in the evolution of a postcolonial identity, and these performative processes may be useftilly considered as exposing the fluidity of national identity and narratives of the nation. The work concentrates predominantly on the textual interactions of theatricality and the cinematic and my methodological approach is broadly deconstructive, as it applies grammatological practices to the cultural discourses analysed. Two groups of films have been selected for their relevance to the subject, both to mark changes in the representations, and to reflect the moments in Irish cinema history when members of the National Theatre Society did the greatest - and most intensive - amount of work in film.
Keywords: Film Studies, Ph.D.; Ph.D. Trinity College Dublin